Choice of flexible functional form in total factor productivity measurement. - Tan, Melvyn Chwee Hock. (2009)
This thesis makes a number of contributions to productivity measurement in the Singapore context. First, a single output, four input panel database is developed thirty manufacturing industries at the 3 Digit Singapore Standard Industrial Classification level from 1980 to 1991. The second contribution is to allow for a more general specification of the cost function. Three competing flexible functional forms: the Transcendental Logarithmic cost function; the Generalised Leontief cost function; and the Symmetric Generalised McFadden cost function are estimated. This allows for a comparison across functional forms. Given the flexibility of the cost functions, economic effects such as returns to scale and technical change can be obtained directly. Last, theory suggests that any flexible functional form can provide a second order approximation to an unknown technology. Here, a non-nested hypothesis test, the PE test is used to determine the appropriate form of the cost function for the Singapore manufacturing sector.